ANALYSIS OF GOOD GOVERNANCE IN CIPAKU VILLAGE GOVERNMENT MREBET DISTRICT, PURBALINGGA DISTRICT - Putri Puja Lasenda; Taufik Purboyo; Oti Kusumaningsih (DYNAMICS: Journal of Public Administration, 2023)
This research is entitled "Good Governance in Cipaku Village Government, Mrebet District, Purbalingga Regency". The purpose of this study was to describe and explain Good Governance in the Cipaku Village Government, Mrebet District, Purbalingga Regency. This research was conducted at the Cipaku Village Government Office, Mrebet District, Purbalingga Regency. This research method is descriptive qualitative. Informants were determined by purposive sampling method. The analysis of research results using an interactive analysis model. Based on the results of the study, several conclusions can be drawn as follows (1). Aspects of Simplicity, Aspects of Participation, the community is given the opportunity to participate in the administration of village government through hamlet meetings, through musdes and musren Bangkes, monitoring mechanisms carried out by the community with meetings that are routine every month evaluating the course of the village government and responding to all problems that occur in society; (2). Legal Rules, providing services based on applicable rules in the form of village regulations, village heads, regional regulations and regional regulations, in carrying out services to the community, prioritizing the community regardless of working hours; (3). In terms of transparency, the community is given the flexibility to be able to access information through information boards and provide information through village deliberations or village institutions, (4). Aspect of Capability, the Village Government can absorb the aspirations of the community by attending meetings in each RT/RW. Development priorities by implementing the Musdus, Musdes and Musrembangdes; (5). Aspects of consensus, the way in which community components participate in making policies through the Musdes and policy decisions made by the village government are left entirely to the deliberation participants to explore the aspirations of the community; (6). Aspect of Justice, in exploring the aspirations of the community in development activities by inviting all components of the community in the village by involving all stakeholders and every planning, implementation, monitoring and evaluation of activities; (7). Effectiveness and Efficiency Aspects of the village government's efforts in optimizing resources in the implementation of development must have clear indicators of achievement, strategies for achieving them and how to solve them if there are problems in their implementation; (8). Aspects of Accountability, accountability for the implementation of the village government is carried out through the Village Government Implementation Report (LPPD) submitted to the Regent and the Accountability Statement Report (LKPJ) submitted to the community through the BPD so far in accordance with applicable regulations /laws.